Digital Signature Method to Overcome Sniffing Attacks on LoRaWAN Network - Lestari, Rahayu Indah; Suryani, Vera; Wardhana, Aulia Arif (International Journal of Electrical and Computer Engineering Systems, 2022)
LoRa or Long Range with LoRaWAN technology is a protocol for low-power wireless networks. The absence of an encryption process on the data payload becomes a challenge for the LoRaWAN network. When the process of sending messages is running inter devices, sniffing might occur, thereby reducing the confidentiality aspect of the data communication process. This paper optimized the digital signature method to secure messages sent by LoRaWAN network devices, along with Advanced Encryption Standard (AES) algorithm and Ed25519 algorithm. AES was used for message encryption, while Ed25519 was used for signature purposes. The aim of applying digital signatures in this paper was to verify that the payload data sent was original and not changed during the transmission process and to ensure data confidentiality. The addition of security mechanisms to the LoRaWAN network, such as the process of encryption, decryption, and verification results, has caused some overheads. The overhead caused by the usage of a digital signature is also analyzed to ensure that the digital signature is feasible to be implemented in LoRa devices. Based on the experimental results, it was found that there was an increase in the size of memory usage and some additional processing delay during the deployment of digital signatures for LoRa devices. The overall overhead caused by implementing digital signatures on the LoRa devices was relatively low, making it possible to implement it on the LoRa network widely.